DESTINATION BENCHMARKING AS AN EFFECTIVE TOOL FOR SUSTAINABLE TOURISM DEVELOPMENT (JURNAL KEPARIWISATAAN, 2010)
Developing sustainable tourism which can help destinations to increase the benefits and minimize the risks of the tourism industry is still becoming a challenge for the tourism authorities in some countries. Destination benchmarking is one of the programmes that give further knowledge and skill about how to develop sustainable tourism. Therefore, this paper will discuss the benefits of destination benchmarking as an effective tool for sustainable tourism in terms of chance to learn from others, maintaining competitive performances and increasing tourist destination profitability. Hence, it is suggested that the destination authorities in Indonesia join the destination benchmarking programme in order to improve tourist destination performances and to develop sustainable tourism in Indonesia.